KIRK HADİSLE MODEL İNSAN - Yerkazan, Hasan (Fırat University, 2018)
“Kırk hadis”, genellikle belli bir konuda kırk hadis ihtiva eden eserlerin ortak adıdır. Bu çalışmalar, belli konularda faydalı olacağı düşünülen hadislerin bir araya getirilmesiyle oluşmaktadır. Bu sahada bugüne kadar itikâd, âhiret, fıkıh, zühd, ahlâk, zikir ve duâ gibi farklı konularda çok sayıda çalışma yapılmıştır. Ayrıca hadis ilimleriyle ilgilenen birçok âlimin bu alanda mütevazi bir eseri bulunmaktadır. Bu çalışmada ise Hz. Peygamber’in sav model insan olma yönü ile ilgili kırk hadis bir araya getirilerek yorumlanmaya çalışılmıştır. Hadisler, onun sosyal hayatta örnek olma yönünü ile ilgili rivâyetlerden seçilmiştir. Her bir hadis, kişinin model insan olma yolunda takip etmesi gereken bir hususa işaret etmektedir. Çalışma neticesinde kırk hadis bağlamında model insan inşasının mümkün olabileceği görülmüştür

“Forty hadith” is the common name of works containing forty hadiths usually on a certain topic. These works are formed by bringing together the hadiths that are thought to be useful in certain matters. Until today, there have been many studies on different subjects such as faith, afterlife, Islamic jurisprudence, asceticism, moral, invocation, and prayer. In addition, many wises interested in hadith scholars have a modest work in this regard. In this study, forty hadiths related to Prophet's Peace be upon him aspect of being a model person were put together and interpreted. The hadiths were selected from narratives about his example in social life. Each hadith indicates a point that one must follow in order to become a model person. As a result of this study, it has been seen that model human construction can be possible in the context of forty hadiths
MODEL HUMAN WITH FORTY HADITH